PENGARUH GERAKAN LITERASI SEKOLAH TERHADAP PENINGKATAN MINAT BACA SISWA KELAS IV SD NEGERI 2 LANDUNGSARI - Nur Alfiana, Dewi Rizka; Nurazizah, Rifqi Aulia; Arviana, Via (Jurnal Pendidikan Dasar dan Keguruan, 2023)
The aim of this research was to find the influence of Gerakan Literasi Sekolah (GLS) towards students’ reading interest in fourth grade of SDN 2 Landungsari. By applying 15 minutes reading before learning, this research was expected to increase students’ reading interest which was still categorized as low. The research method used was descriptive quantitative with associative approach. Fourth grader students of SDN 2 Landungsari was the population of this research consist of 17 students. This research was using population study which the subject was the whole population of fourth grader students of SDN 2 Landungsari. The data collected by distributing multiple choice and essai Pre-test and Post test questions. The data was analyzed by using ANOVA simple linear regression analysis in SPSS 25 for Windows. The result shows that there was a significant effect from Gerakan Literasi Sekolah (GLS) on increasing students’ of fourth grade reading interest at SDN 2 Landungsari, Dau, school year 2022/2023.